Water temperature and biological sex influence cold pressor pain in healthy adults: a randomized within-subjects trial - Goreis, Andreas; Fanninger, Selina; Lozar, Annika; Mayer, Anna; Pfatrisch, Nina; Voracek, Martin; Plener, Paul L.; Kothgassner, Oswald D. (Frontiers in Physiology, 2025)
The Cold Pressor Test (CPT) is an established method for evaluating pain perception and stress responses; evidence indicates that females perceive the CPT as more painful than males. However, methodological variations—particularly in water temperature—complicate cross-study comparisons and hinder robust study designs. To address these issues, we examined the effects of three water temperatures (1°C, 3°C, and 6°C) on pain outcomes and physiological stress markers (heart rate [HR] and heart rate variability [HRV]) in healthy adults while exploring sex differences. In a randomized, single-blind, within-subjects trial with 148 participants (68% female), the CPT was administered using a temperature-controlled cooling device with continuous circulation. Participants immersed their dominant hand for up to 3 min, when the trial was terminated. Pain threshold, tolerance, and intensity were recorded alongside HR and HRV. Results revealed significant variations in pain threshold, tolerance, and intensity across temperatures, with lower temperatures eliciting increased pain perception (medium effect sizes). Males demonstrated higher pain tolerance in 1°C and 3°C conditions, with 50% reaching the 3-min cutoff, compared to 39% at 6°C, 23% at 3°C, and 19% at 1°C for females. No significant sex differences were observed for pain intensity, and HR and HRV did not vary across temperatures or between sexes. However, pain was associated with HR and HRV only in males. Our findings underscore the need for meticulous CPT protocol design. Controlling water temperature and implementing appropriate stopping rules—potentially extending beyond 3 min—are critical for improving comparability, replicability, and understanding of pain mechanisms in healthy populations overall.